European multicentre study on outcome of surgery for sporadic primary hyperparathyroidism. Issue 6 (17th September 2020) - Bergenfelz, A; van Slycke, S; Makay, Ö; Brunaud, L
Abstract : Some 5861 patients undergoing first‐time surgery for sporadic primary hyperparathyroidism were registered in the Eurocrine ® database between 2015 and 2018. The use of intraoperative parathyroid hormone measurement decreased the risk of conversion and persistent hypercalcaemia. The use of two or three localization procedures decreased the risk of persistent hypercalcaemia; the risk of persistent hypercalcaemia was low in patients with a concordant single lesion. Outcome is very good Abstract: Background: International multicentre outcome studies of surgery for primary hyperparathyroidism (pHPT), especially for rate of conversion to bilateral neck surgery and persistent hypercalcaemia, are scarce. Methods: Eurocrine ® is a European database for endocrine surgery. Data are entered according to predefined data fields. Outcomes for patients who underwent first surgery for sporadic pHPT were analysed. Multivariable analysis was performed to identify risk factors for adverse outcome using Cox regression with constant follow‐up. Results: A total of 5861 patients were registered between 2015 and 2018. Preoperative localization procedures were used in most patients, with moderate sensitivity. Intraoperative parathyroid hormone (ioPTH) measurement was used in three‐quarters of patients. Bilateral surgery was performed in 1574 patients (26·9 per cent). Among 4683 patients (79·7 per cent) for whom unilateral or focused operation was planned, the procedure was converted to bilateral surgery in 396 (8·5 per cent). The risk of conversion decreased with the use of ioPTH monitoring (relative risk (RR) 0·77). Persistent hypercalcaemia was registered in 253 patients (4·3 per cent), and was less likely with the use of two (RR 0·55) or three (RR 0·44) localization procedures. In patients with a concordant localized single lesion, the rate of persistent hypercalcaemia was 2·5 per cent. The risk of persistent hypercalcaemia decreased with the use of ioPTH measurement, but was increased in patients with negative localization procedures and conversion to bilateral surgery. Conclusion: The use of ioPTH measurement decreased the risk of conversion and persistent hypercalcaemia. The use of two or three localization procedures decreased the risk of persistent hypercalcaemia; in patients with a concordant single lesion, the risk of persistent hypercalcaemia was low.